On using fourier series in characterizing particle shape - 355381 Bandemer, Hans; Albrecht, Matthias; Kraut, Andre
This paper starts from the fact that the Fourier coefficients of the contour of a particle are commonly used to describe its shape, for example by Meloy's law of morphological coefficients. The authors point to the sensitivity of the Fourier coefficients to jump discontinuities of the contour or of one of its derivatives. Explicit formulae for this dependence are reported and are used to suggest a stochastic model, the sensitivity is demonstrated by two examples with calculated results.